Global social and environmental change drives the management and delivery of ecosystem services from urban gardens: A case study from Central Coast, California. (January 2020) - Lin, Brenda B.; Egerer, Monika H.
Highlights: We synthesize three years of research in urban community gardens in Central Coast, California. Global social and environmental change factors impact management and delivery of ecosystem services. Garden regulations and management decisions by gardeners determine the ecological complexity of gardens. Ecological complexity can affect the ecosystem service, such as food provision, coming from gardens. Active management can increase social-ecological outcomes that feedback to the larger system. Abstract: Urban community gardens are vital green spaces threatened by global social and environmental change factors. Population growth has reduced the amount of space available in cities, and climate change challenges plant growth thresholds. Urban community gardens provide dynamic socio-ecological systems to study how such social and environmental change factors affect the management and delivery of ecosystem services. They provide spaces where urban citizens purposefully interact with nature and receive multiple benefits. In this paper, we synthesize the results of three years of research in a case study of urban community gardens across the Central Coast of California and present a framework showing how both social and environmental change factors at the regional scale affect the ecological make-up of urban community gardens, which in turn affect the ecosystem services coming from such systems. Our study reveals that global environmental change felt at the regional level (e.g., increased built environment, climate change) interact with social change and policy (e.g., population growth, urbanization, water use policy), thus affecting regulations over garden resources (e.g., water availability) and management decisions by gardeners (e.g., soil management, crop planting decisions). These management decisions at the plot-scale, determine the ecological complexity and quality of the gardens and affect the resulting ecosystem services that come from these systems, such as food provision for both humans and urban animals. A greater understanding of how environmental and social change factors drive the management processes of urban community gardens is necessary to design policy support systems that encourage the continued use and benefits arising from such green spaces. Policies that can support urban community gardens to maintain ecological complexity and increase biodiversity through active management of soil quality and plant diversity have the potential to increase social and environmental outcomes that feedback to the larger environmental and social system.